Kajian Kriminologis Tentang Perkelahian Antar Anak (Studi Kasus Kecamatan Wearinama, Kabupaten Seram Bagian Timur) - Rumadan, Salmiwati; Supusepa, Remon; Makaruku, Steven (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Criminological study of fights between children in Werinama sub-district. Understanding child delinquency or Jusvenile delinquency of children's delinquency is an act or behavior that is anti-social.Purposes of the Research: This study uses an empirical method with legal materials used in the study are primary, secondary and tertiary with the use of observation techniques, interviews and documentation.Methods of the Research: The type of research used is empirical by looking the provisions realiting to the in the field, which is obtained from observatins and interview with key informants. The problem apporoach is the statute apporoach and the apporoach in accordance with the reality on the ground . the collection of legal materials throug primary legal materials is then linked to secndry legal materials . management and analysis f legal materials decribed qualitatively.Results of the Research: General description of the research location, the Werinama Bearda sub-district on Seram Island, and directly adjacent to the West Bula sub-district in the North, Banda Laut in the South, Kilmury in the east and borders with Siwalalat sub-district in the west side of fights between children in the Werinama Bersal sub-district from mutual grudge, mutual ridicule, misunderstanding, child delinquency. Efforts to resolve fights between children, namely through the Pre-emprit method, are efforts or efforts to prevent crime from the start, carried out by the police in which the action is psychological or moral in nature. The preventive method is an effort carried out with the aim of preventing the occurrence of crime by means of control and supervision, and the Repressive Method is an effort or action taken directly to eradicate violent crimes such as persecution by providing measures so that the treatment is deterred and does not return the crime.